(untitled) (Olhar de Professor, 2023)
This article presents reflections on the supervised internship and pedagogical residency in the remote teaching modality, based on experiences in the early elementary school years at Colégio de Aplicação (school lab) of the Federal University of Roraima (CAp/UFRR), in the academic years of 2020 and 2021. This research aims to discuss the didactic-methodological challenges of supervised internship and pedagogical residency in this teaching modality. It has a qualitative approach, and it is characterized as an explanatory-descriptive study. The data-collection tools used were field diary, videoconferences, and reports. The results have shown that, in the face of the pandemic scenario, the supervised internship and the pedagogical residency underwent adaptations to fulfill academic and educational demands, such as: constituted themselves as a dynamic and active space for initial teacher training; they provided action-reflection on the school curriculum and brought implications for the teaching-learning processes and the student’s real needs, especially in extreme contexts.